Realising value from projects: a performance-based analysis of determinants of successful realisation of project benefits. (2016) - Mohan, Kunal; Ahlemann, Frederik; Braun, Jessica
The successful realisation of value (i.e., benefits) from information technology (IT) investments has consistently been reported as one of the major organisational challenges because it generally falls short of expectations. From a project perspective, we examine which factors are necessary to realise IS developments' anticipated value. To better understand the role of benefits management (BM) determinants and their impact on successful benefits realisation, we apply partial least squares (PLS) technique on data collected from 456 individuals. We find that currently the greatest potential to increase the probability of successful benefits realisation lies in the improvement of the ability to continuously review the status of benefits realisation in projects. On the other hand, we find that providing project stakeholders with incentives to align their individual goals and interests towards the common objective of realising planned project benefits is perceived to be not very effective.